Effectiveness of A-Ba-Te Innovation (Let's Eradicate Tuberculosis) on Self-Care Management among TB Patients in Public Health Center - Hidayat, Taofik; Janah, Esti Nur; Rohmiati, Marti Dwi; Umami, Fasikhatul (STIKep PPNI Jawa Barat, 2024)
Aims: This study examines the effectiveness of the A-Ba-Te innovation in promoting self-care among TB patients in the Sirampog Health Center service area. Methods: A quasi-experimental design with one group was observed on the dependent variable after intervention (one group pretest-posttest design). The study involved 22 respondents who received treatment at the Sirampog Health Center over four weeks. They were given the